A case report on acrania with omphalocele - D., Rita; B., Tejaswinibandaru (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Congenital/fetal malformations are structural, functional, and/or biochemical molecular defects present at birth. Prevalence of congenital fetal anomalies in developing countries are 2 to 3% of newborns and about 94% of severe birth defects. Acrania is a lethal congenital malformation characterized by partial or complete absence of flat bones in cranial vault. Another anomaly, omphalocele, a ventral defect of the umbilical ring resulting in herniation of the abdominal viscera, is one of the most common congenital abdominal wall defects seen in the newborn. Omphalocele is associated with trisomy. Incidence of acrania in India 1.4 to 2 per 1000 births. Incidence of omphalocele 1 in 4000 births. a case of 29-year-old, G2P1L1 with 14 weeks 2 days of gestation attended OPD with ultrasonographic report showing acrania with omphalocele. The sonographic scan revealed fully developed fetal brain having no calvarium. The brain was covered by a thin membranous structure. Facial structures showing frog eye appearance, open spina bifida. Normal and well-coordinated movements were noted in in the fetal body parts. The fetal abdomen showed a central mass protruding out from anterior abdominal wall. The mass is covered by a membrane and contains small intestines. There was direct insertion of the umbilical cord into the midline of omphalocele. Patient was counselled regarding fetal condition and its outcome. Patient was willing for termination. Medical termination of pregnancy was done. A single dead female fetus of fetus and placental weighing of 250 gm.